Enteroendocrine cell regulation of the gut-brain axis - Barton, Joshua R.; Londregan, Annie K.; Alexander, Tyler D.; Entezari, Ariana A.; Covarrubias, Manuel; Waldman, Scott A. (Frontiers in Neuroscience, 2023)
Enteroendocrine cells (EECs) are an essential interface between the gut and brain that communicate signals about nutrients, pain, and even information from our microbiome. EECs are hormone-producing cells expressed throughout the gastrointestinal epithelium and have been leveraged by pharmaceuticals like semaglutide (Ozempic, Wegovy), terzepatide (Mounjaro), and retatrutide (Phase 2) for diabetes and weight control, and linaclotide (Linzess) to treat irritable bowel syndrome (IBS) and visceral pain. This review focuses on role of intestinal EECs to communicate signals from the gut lumen to the brain. Canonically, EECs communicate information about the intestinal environment through a variety of hormones, dividing EECs into separate classes based on the hormone each cell type secretes. Recent studies have revealed more diverse hormone profiles and communication modalities for EECs including direct synaptic communication with peripheral neurons. EECs known as neuropod cells rapidly relay signals from gut to brain via a direct communication with vagal and primary sensory neurons. Further, this review discusses the complex information processing machinery within EECs, including receptors that transduce intraluminal signals and the ion channel complement that govern initiation and propagation of these signals. Deeper understanding of EEC physiology is necessary to safely treat devastating and pervasive conditions like irritable bowel syndrome and obesity.